EFL Students’ Attitudes Towards Autonomous Learning Through Busuu: A Mobile Application - Rizqiyyah, Rizqiyyah; Drajati, Nur Arifah (Universitas Islam Negeri Raden Intan Lampung, 2020)
Studies on the appliances of mobile phones have indicated a positive effect on language improvement. This case study attempts to explicate students' perceptions of autonomous learning through Busuu (a language mobile application). The subjects of this study were 17 females and three males of an English language center at a university in Indonesia. The result showed that the use of the Busuu app supported learners’ autonomy. (1) Students controlled over learning management freely managing their time to study and got motivated more to learn English after accessing the app. The findings indicated that the lower the level of competence in English, the longer students spent their time to access the app. (2) Students controlled over cognitive processing by showing their interest in vocabulary practices. Next, students controlled over learning content by selecting which material to study first so that they were able to meet their expectations of accessing the app. At last, (3) students controlled over learning strategies by reflecting on how well they have learned from the automated feedback feature provided in the app. To sum up, students have a positive attitude towards the app in that it helps them enhance their English proficiency skills, especially in vocabulary enrichment.